Sanksi Adat Istiadat Cepalo Tigo terhadap Pelaku Zina Perspektif Al-Mashlahah Mursalah (Studi desa Rawa Indah Kecamatan Ilir Talo Kabupaten Seluma) - Hanif, Ridwan; Rohimin, Rohimin; Rohmadi, Rohmadi (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract : This research has several problems, first, how to implement the cepalo tigo customary sanctions against adulterers in Rawa Indah Village, Ilir Talo District, Seluma Regency. Second, what is the view of Islamic law regarding customary sanctions against perpetrators of adultery from the perspective of al-mashlahah murlah in Rawa Indah Village, Ilir Talo District, Seluma Regency. The method used in this research is field research, where data has been collected through interviews, observation and documentation. The results of this research show that the customary sanctions made by the leaders of the Rawa Indah village in Seluma Regency are as follows: First, the perpetrator of adultery is given a fine. Second, the fine is used to buy goats and for village social causes. Third, the goat is slaughtered and then its blood is sprinkled in the four corners of the village. In the customary sanctions against perpetrators of adultery there is still an element of shirk because there is blood being sprinkled in the four corners of the village to fence off the village to avoid this disgraceful act. The three sanctions that still contain shirk should be abolished, the fourth is that the benefits and benefits of implementing them are effective, because since the implementation of these sanctions, the number of adulterers has been reduced. Keywords: Customary Sanctions, Perpetrators of Adultery, Al-Mashalahah Mursalah. Abstrak :Pada penelitian ini mempunyai beberapa masalah pertama, Bagaimana pelaksanaan sanksi Adat Istiadat cepalo tigo terhadap pelaku zina di Desa Rawa Indah Kecamatan Ilir Talo Kabupaten Seluma. Kedua Bagaimana Pandangan hukum islam terhadap sanksin adat istiadat terhadap pelaku zina perspektif al-mashlahah mursalah di Desa Rawa Indah Kecamatan Ilir Talo Kabupaten Seluma. Metode yang digunakan dalam penelitian ini adalah penelitian lapangan, dimana data-data telah dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa sanksi adat istiadat yang dibuat oleh tokoh-tokoh desa rawa indah di Kabupaten Seluma sebagai berikut: Pertama, pelaku zina ditetapkan denda. Kedua, denda tersebut digunakan untuk membeli kambing dan untuk sosial desa. Ketiga, kambing tersebut disembelih kemudian darahnya dipercikkan ke empat penjuru desa. Dalam sanksi adat istiadat terhadap pelaku zina masih ada unsur kesyirikan karna adanya memerckkan darah ke empat penjuru desa untuk memagari desa agar terhindar dari perbuatan tercela tersebut. Ketiga sanksi yang masih mengandung kesyirikan mestinya harus ditiadakan, keempat kemaslahatan dan kemanfaatannya diberlakukan sanksinya termasuk efektif karna semenjak dilaksanakannya sanksi tersebut telah mengurangi angka pelaku zina. Kata kunci : Sanksi Adat Istiadat, Pelaku Zina, Al-Mashalahah Mursalah.